2017
DOI: 10.1186/s12917-017-1310-2
|View full text |Cite
|
Sign up to set email alerts
|

Birth delivery method affects expression of immune genes in lung and jejunum tissue of neonatal beef calves

Abstract: BackgroundCaesarean section is a routine veterinary obstetrical procedure employed to alleviate dystocia in cattle. However, CS, particularly before the onset of labour, is known to negatively affect neonatal respiration and metabolic adaptation in humans, though there is little published information for cattle. The aim of this study was to investigate the effect of elective caesarean section (ECS) or normal trans-vaginal (TV) delivery, on lung and jejunal gene expression profiles of neonatal calves.ResultsPat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…One of the few studies conducted in calves describes down-regulated mRNA expression levels for several TLRs and antimicrobial peptides in the small intestine in the weeks after birth compared to calves at 6 months 16 . Additionally, IL1 and IL6 gene expression in the calf jejunum has been recently shown to be affected by method of birth 17 . In cattle, FAE of Peyer's patches have a critical role in trafficking not only colostral leukocytes into neonatal circulation 18 but also infectious disease antigens including mycobacteria and thereby play a critical role in the immune response to these agents 19 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the few studies conducted in calves describes down-regulated mRNA expression levels for several TLRs and antimicrobial peptides in the small intestine in the weeks after birth compared to calves at 6 months 16 . Additionally, IL1 and IL6 gene expression in the calf jejunum has been recently shown to be affected by method of birth 17 . In cattle, FAE of Peyer's patches have a critical role in trafficking not only colostral leukocytes into neonatal circulation 18 but also infectious disease antigens including mycobacteria and thereby play a critical role in the immune response to these agents 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study was performed using a single early-life intervention with an ecological context, consisting of two alternative modes of delivery, followed by a long-term high-resolution sampling effort performed in a controlled environment. One-third of the animal cohort was delivered via C-section and the rest through the birth canal, creating conditions that exposed the animals to different species pools via the maternal microbiome 19,30,31 . Following this intervention, we documented the microbiome dynamics of 45 animals over the course of up to 3 years, reared under the same conditions and sampled at high resolution, whereby a third of the cohort was sampled over a 3-year period.…”
mentioning
confidence: 99%
“…In addition, the development of the intestinal lumen and gastrointestinal peristalsis in premature infants are not perfect, the digestion and hydrolysis of various pathogens and toxins are inadequate, and intestinal peristalsis is slow, which allows food to accumulate in the intestine. This accumulation can lead to gastrointestinal damage, bacterial overgrowth and intestinal flatulence, resulting in the occurrence of NEC[ 6 , 7 ]. On the other hand, studies have shown that hypoxia-ischemia and reperfusion injury to the intestinal wall are also important factors that lead to the occurrence of NEC.…”
Section: Discussionmentioning
confidence: 99%